Key Characteristics of Employment Regulations in the Middle East and North Africa - Angel-Urdinola, Diego F. (World Bank, Washington, DC, 2012)
This Fast Brief provides a general background on the main features of labor regulations in the Middle East and North Africa (MENA) Region. This is part of an effort to understand employability constraints in MENA and to this end a World Bank team gathered information on labor legislation and other legal acts concerning labor regulations in the region. All this rendered more urgent with the ongoing social and political turmoil in the region. Within the broader scope of labor regulations, and in order to assure regional comparability, the information that was collected focused on key issues associated with commencing or terminating employment and during the period of employment (including maternity benefits). This Brief is to provide policymakers and international organizations with a regional analysis of how labor regulation affects labor market outcomes in the region and to inform governments on strategic approaches to employment creation through labor policy and associated reforms. This activity comes as a response to regional priorities in the context of the Arab World Initiative (AWI): one of the six strategic themes of the AWI focuses explicitly on employment creation as a top priority.